2020
DOI: 10.1016/j.sleep.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Improved night shift schedule related to the mortality of critically ill patients with Corona Virus Disease 2019

Abstract: Purpose To determine the relationship between the improved night shift schedule and the mortality of critically ill patients with Corona Virus Disease 2019 (COVID-19). Methods According to the time of the implementation of the new night shift schedule, we divided all patients into two groups: initial period group and recent period group. The clinical electronic medical records, nursing records, laboratory findings, and radiological examinations for all patients with lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“… 74 , 75 A recent single-center, retrospective study showed that implementation of new night shift schedule, changing from a four-day cycle to only daytime work for doctors with emergency techniques and extensive first aid experience and a six-day cycle in other doctors and nurses, significantly decreased the mortality of critically ill patients with COVID-19. 76 Thus, more reasonable shift working schedules that allow for adequate rest for HWs and at the same time, ensure the continuity of treatments for patients, should be highly recommended during COVID-19 emergency status. 76 , 77 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 74 , 75 A recent single-center, retrospective study showed that implementation of new night shift schedule, changing from a four-day cycle to only daytime work for doctors with emergency techniques and extensive first aid experience and a six-day cycle in other doctors and nurses, significantly decreased the mortality of critically ill patients with COVID-19. 76 Thus, more reasonable shift working schedules that allow for adequate rest for HWs and at the same time, ensure the continuity of treatments for patients, should be highly recommended during COVID-19 emergency status. 76 , 77 …”
Section: Resultsmentioning
confidence: 99%
“… 76 Thus, more reasonable shift working schedules that allow for adequate rest for HWs and at the same time, ensure the continuity of treatments for patients, should be highly recommended during COVID-19 emergency status. 76 , 77 …”
Section: Resultsmentioning
confidence: 99%
“…Long night shifts can disrupt homeostasis and circadian rhythms, disrupt the levels of several hormones (e.g., melatonin and cortisol), cause sleep deprivation, increase the chances of errors at work (Ballesio et al, 2021), and even increase the risk of infection (Lim et al, 2020). A new night shift schedule was tested in Wuhan, China, wherein doctors who were skilled in emergency techniques and had extensive first aid experience were only needed to work during the day, thus allowing them sufficient rest time, whereas for other doctors, their prior schedule was changed to ensure fewer night shift hours and was aligned with the already in‐practice schedule of the nurses (Zhang, Xu, et al, 2020). The results showed that this scheduling approach effectively improved the sleep quality of healthcare workers and increased the survival rate of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gender 8 (Ali et al, 2021;Cai et al, 2020;Wei et al, 2020;Xu et al, 2021;Yin et al, 2021;Zhan et al, 2020;Zheng et al, 2021) 79 in-practice schedule of the nurses (Zhang, Xu, et al, 2020). Worried about being infected 3 (Chen, Ma, et al, 2021;Deng et al, 2020;Zhang, Yang, et al, 2020) 4.9% rience (Wang, Hu, et al, 2020;Wang, Huang, et al, 2020;Wang, Ren, et al, 2020) and translate into poor readiness to cope with the crisis (Zhou et al, 2020) turn exacerbates these negative emotions, leading to a vicious cycle (Ballesio et al, 2021).…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…23,24 The abovementioned external environment and these symptoms may affect the sleep duration and quality of patients, especially those with primary hypertension complicated with COVID-19 infection. 25,26 These patients are more likely to have blood pressure fluctuations and even develop hypertension urgencies. Hypertension urgencies is a group of clinical syndromes caused by an acute increase in blood pressure with or without damage to target organs.…”
Section: Discussionmentioning
confidence: 99%